Proteome Response of Staphylococcus xylosus DSM 20266T to Anaerobiosis and Nitrite Exposure - Quintieri, Laura; Giribaldi, Marzia; Giuffrida, Maria Gabriella; Creanza, Teresa Maria; Ancona, Nicola; Cavallarin, Laura; De Angelis, Maria; Caputo, Leonardo (Frontiers in Microbiology, 2018)
The viability and competitiveness of Staphylococcus xylosus in meat mostly depend on the ability to adapt itself to rapid oxygen and nutrients depletion during meat fermentation. The utilization of nitrite instead of oxygen becomes a successful strategy for this strain to improve its performance in anaerobiosis; however, metabolic pathways of this strain underlying this adaptation, are partially known. The aim of this study was to provide an overview on proteomic changes of S. xylosus DSM20266Tcultured under anaerobiosis and nitrite exposure. Thus, two different cultures of this strain, supplemented or not with nitrite, were in vitro incubated in aerobiosis and anaerobiosis monitoring cell viability, pH, oxidation reduction potential and nitrite content. Protein extracts, obtained from cells collected as nitrite content was depleted, were analysed by 2DE/MALDI-TOF/TOF-MS. Results showed that DSM20266T growth was significantly sustained by nitrite in anaerobiosis, whereas no differences were found in aerobiosis. Accordingly, nitrite content was depleted after 13 hours only in anaerobiosis. At this time of sampling, a comparative proteomic analysis showed 45 differentially expressed proteins. Most differences were found between aerobic and anaerobic cultures without nitrite; the induction of glycolytic enzymes and glyoxylate cycle, the reduction of TCA enzymes, and acetate fermentation were found in anaerobiosis to produce ATP and maintain the cell redox balance. In anaerobic cultures the nitrite supplementation partially restored TCA cycle, and reduced the amount of glycolytic enzymes.These results were confirmed by phenotypic microarray that for the first time was carried out on cell previously adapted at the different growth conditions; overall, metabolic changes were similar between aerobiosis and anaerobiosis NO2-adapted cells, whilst cells grown under anaerobiosis showed different assimilation profiles by confirming proteomic data anaerobic; indeed, these latter extensively assimilated substrates addressed at both supplying glucose for glycolysis or fuelling alternative pathways to TCA cycle. In conclusion, metabolic pathways underlying the ability of S. xylosus to adapt itself to oxygen starvation were revealed; the addition of nitrite allowed S. xylosus to take advantage of nitrite to this condition, restoring some metabolic pathway underlying aerobic behaviour of the strain.